Drosophila Photo-transduction Simulator. (14th April 2013) - Nikolic, Konstantin; Loizu, Joaquim
This software contains detailed modelling of the single photon response, the quantum bump, of fly photoreceptors. All known components participating in the primary phototransduction process are taken into account, and estimates are given for both the physical and chemical parameters. Both deterministic and stochastic simulations of the photoinduced current are possible using the same software. The code was implemented in Matlab and stored at the Imperial College London repository. It includes a GUI which offers an easy access and manipulation of the input parameters and therefore allows for simulations for a vast number of interesting possibilities, such as various mutants, different ionic concentrations, etc. Explanations for all the equations and parameters used are given in ref. [1 ].